Spain : Selected Background Issues. (IMF Staff Country Reports; Country Report ;, 1995)
This Selected Background Issues paper examines different aspects of the social security system in Spain. The paper describes the role of this system in the process of consolidating the government finances in the short- and medium-term, and to present possible measures to address the policy challenges of the longer term. An analysis of the finances of the social security system is presented. The paper provides a description of the main features of the pension system and projections of its financial situation in the long term.